ESTIMATING COST CONTINGENCY FOR CONSTRUCTION PROJECTS: THE CHALLENGE OF SYSTEMIC AND PROJECT SPECIFIC RISK - J.I.T Buertey; Emmanuel Abeere-Inga; Theophilus Adjei Kumi (Journal of Construction Project Management and Innovation)
The challenge of poor scope definition resulting in scope creep is recognized as the major driver for construction project and cost overruns. All construction projects are associated with both systemic uncertainty and project specific uncertainty. The epistemic ambiguity in risk estimation could be considered as an opportunity or threat, a gain or loss, positive or negative; while project specific risk are in relation to project cost which makes its estimation untoward. Out of 204 questionnaires distributed to the Built Environment Professionals to determine the impact of systemic and project specific risk factors on the estimation of cost contingency, 118 were retrieved representing 57.8%. Data analysis using FMEA as a qualitative risk tool and univariate statistical analysis as a quantitative risk tool revealed that systemic risk accounted for approximately 64% of the cost drivers related of the construction cost uncertainty whilst projects specific risk accounted for 36% of the risk impact. Scope changes, incomplete scope definition, design status and changes in specification were revealed as high-impact systemic risk which has a high propensity of cost overrun effect on cost contingency. The impact of systemic risks can be managed through a design management effort by confirming the certainty of owner related issues during project definition and planning stage through historical based models relying on organizational process asset. The research revealed that the effect of project specific risk including natural and force majeure conditions and economic indicators are beyond the prediction and stochasticity effort of the project team. Project specific risk can be managed only through collaborative communicative effort of the project team with simulation to enable the right construction technologies to be selected and risk impact to be curtailed.